Entretien avec Ouédraogo Souley (Migration Control, Violence and Covid 19: (Im)Mobility Regimes in the Borderlands of Burkina Faso, Benin and Niger, 2023)
Impacts of COVID-19 on cross-border movements of populations in the eastern region of Burkina Faso, Benin and Niger.
Keywords: Emigration and immigration; Border security; Violence; Terrorism; Migration Control; (Im)mobility; Impact; Border; Migration; COVID-19 Pandemic